Hoover Damn: Land, Labor, and Settler Colonial Cultural Production. (February 2017) - Griffith, Jane
Hoover Dam is a settler-colonial project, requiring Indigenous land and waterways while producing energy that enables further non-Indigenous settlement. In addition to the Dam's engineering feats, its cultural production—art, pageantry, commemoration, and media—helped to buttress these claims to land. In this article, I offer the concept of dam/ning: how tactics used to preserve White settler memory, history, and claims to land and water seemingly appear to affirm Black and Indigenous lives but in fact veil violence. Also embedded in the term is damning: the strategies used to resist settler-colonial violence, dehumanization, displacement, and land theft. Dam/ning analyzes whose land these actions take place on, who claims this land and how, and what techniques people have used to resist. I draw from a tripartite archive: personal letters from Hoover Dam's official artist (1920s-1940s), the Bureau of Reclamation's magazine (1930s), and the town site's local newspaper (1979). This article begins by establishing the practices of damming—the physical and cultural practices that enabled White settlement, which denigrated Indigenous and Black peoples while requiring their knowledge, art, and bodies; the second half of the article establishes the practices of damning, exposing ways Indigenous and Black communities fought these settler-colonial practices throughout the 20th century.